Visualisasi Decision Making MAGIQ melalui GAIA Biplot: Kasus Permohonan Paten - Erlin Windia Ambarsari; Sri Melati Sagita; Dudi Parulian (STMIK Budi Darma, 2023)
Data visualization and Multi-criteria Decision Making (MCDM) are crucial in analyzing and interpreting complex data and supporting data-based decision-making processes. This research integrates MAGIQ, an MCDM approach, with Improved Rank Order Centroid (IROC) weighting and data visualization using the Geometrical Analysis for Interactive Aid (GAIA) biplot. This study aims to understand the relationship between criteria and alternatives in MAGIQ, facilitated by IROC weighting to interpret alternative selection. The research findings indicate that for the 'Patent Description' criterion, the IROC weight value is 0.513401, signifying the importance of this criterion in the assessment context. In the case of alternative P2, the total MAGIQ score obtained is 0.4485124, indicating that P2 is the best alternative based on the given criteria. P1 and P3 received MAGIQ scores of 0.2775665 and 0.2739211, respectively, placing them in the second and third ranks. This research implements the IROC method in MAGIQ in a systematic manner, where specific coefficients are used to calculate the weight of each criterion, and a GAIA biplot is utilized to visualize the relationship between criteria and alternatives. The practical application of this approach can be seen in patent application cases, where decision-makers can use it to evaluate complex alternatives in a more structured and data-based manner